Enantioselective separation of nonsteroidal anti‐inflammatory drugs with amylose tris(3‐chloro‐5‐methylphenylcarbamate) stationary phase in HPLC with a focus on enantiomeric quality control in six pharmaceutical formulations containing racemic mixtures or single stereoisomers. Issue 12 (15th October 2021) - Cao, Shirong; Xie, Chunting; Ma, Qianyun; Wang, Shaoping; Zhang, Jiayu; Wang, Zhaokun
Abstract: In the present study, an accurate, rapid, and simple chiral HPLC‐UV method with amylose tris(3‐chloro‐5‐methylphenylcarbamate) as stationary phase was developed and applied for enantiomeric determination of six nonsteroidal anti‐inflammatory drugs (NSAIDs) in the commercial pharmaceutical formulations, including ( R, S )‐ibuprofen, S‐ibuprofen, ( R, S )‐ketoprofen, S‐ketoprofen, S‐naproxen, and ( R, S )‐loxoprofen sodium. Experiments on the influence of mobile phase composition, proportion of organic modifier, percentage of acid additives, and column temperature on enantioseparation were conducted to obtain the best separation condition. It was indicated that one mobile phase simply composed of acetonitrile‐water (0.1% formic acid, v/v) at the proportion of 50:50 (v/v) with a flow rate of 0.6 ml/min at 22°C could simultaneously provide the excellent enantiomeric resolutions for all selected NSAIDs, which made the enantioseparation process more applicable and operable. The newly developed method was then applied for determination of NSAID enantiomers in pharmaceutical formulations containing racemic mixtures or single stereoisomers. Calibration curve of each enantiomer at the concentration of 5.0–100 ug/ml showed good linearity with the correlation coefficient above 0.9996. Satisfactory recovery (96.54–101.54%), good intra‐day precision (RSD 0.52–1.46%), and inter‐day precision (RSD 0.13–1.09%) were also obtained. The newly developed method was then applied for determination of NSAID enantiomers in pharmaceutical formulations containing racemic mixtures or single stereoisomers. Quantitative results of the commercial capsules and tablets demonstrated that the difference between the declared and measured values did not exceed 1.52%. Abstract : The method was applied for enantiomeric quality control of commercial NSAIDs formulations containing racemic mixtures or single enantiomers.